Positive psychosocial factors may protect against perceived stress in people with systemic lupus erythematosus with and without trauma history - Lindsey A Criswell; Patricia P Katz; Jinoos Yazdany; Maria Dall'Era; Caroline Gordon; Stephanie Rush; Laura Trupin; Cristina Lanata; Kamil E Barbour; Sarah Patterson; Kimberly Dequattro; Kurt J Greenlund (Lupus Science and Medicine)
Objective Trauma history is associated with SLE onset and worse patient-reported outcomes; perceived stress is associated with greater SLE disease activity. Stress perceptions vary in response to life events and may be influenced by psychosocial factors. In an SLE cohort, we examined whether stressful events associated with perceived stress, whether psychosocial factors affected perceived stress, and whether these relationships varied by prior trauma exposure.Methods This is a cross-sectional analysis of data from the California Lupus Epidemiology Study, an adult SLE cohort. Multivariable linear regression analyses controlling for age, gender, educational attainment, income, SLE damage, comorbid conditions, glucocorticoids ≥7.5 mg/day and depression examined associations of recent stressful events (Life Events Inventory) and positive (resilience, self-efficacy, emotional support) and negative (social isolation) psychosocial factors with perceived stress. Analyses were stratified by lifetime trauma history (Brief Trauma Questionnaire (BTQ)) and by adverse childhood experiences (ACEs) in a subset.Results Among 242 individuals with SLE, a greater number of recent stressful events was associated with greater perceived stress (beta (95% CI)=0.20 (0.07 to 0.33), p=0.003). Positive psychosocial factor score representing resilience, self-efficacy and emotional support was associated with lower perceived stress when accounting for number of stressful events (−0.67 (−0.94 to –0.40), p<0.0001); social isolation was associated with higher stress (0.20 (0.14 to 0.25), p<0.0001). In analyses stratified by BTQ trauma and ACEs, associations of psychosocial factors and perceived stress were similar between groups. However, the number of recent stressful events was significantly associated with perceived stress only for people with BTQ trauma (0.17 (0.05 to 0.29), p=0.0077) and ACEs (0.37 (0.15 to 0.58), p=0.0011).Conclusion Enhancing positive and lessening negative psychosocial factors may mitigate deleterious perceived stress, which may improve outcomes in SLE, even among individuals with a history of prior trauma who may be more vulnerable to recent stressful events.